Motivation as a fundamental factor to improve efficiency in health professionals - González Carmona, Leidy Viviana (2023)
Recently, organizations have maximized their efforts to implement continuous improvement plans in Human Resources, recognizing that employees are the central gear for an efficient operation, labor motivation is one of the concerns, since it directly affects performance. For this reason, it is necessary to identify the factors that influence the creation of an optimal organizational climate for the efficient development of activities, considering that this influence is different depending on the sector. The results of this bibliographic review show the influence of work motivation on health care personnel and its relationship with the quality of service that the patient may perceive. The objective of this review was to describe the importance and most relevant aspects of motivation as a factor to improve efficiency in health professionals.